Higgs Domino Island” Game Addiction Among Teenagers In Surabaya - Putra, Surya Jaya Purnama; Suryanto, Suryanto; Meiyuntariningsih, Tatik (International Journal of Research in Counseling, 2022)
The aims of this study were: 1.) to identified forms of addiction, 2.) intensity of addiction, and 3.) factors of games which are sources of addiction. This research uses qualitative and the method used is the case study method. The subjects of this study were teenagers who played the game "Higgs Domino Island" in Surabaya. Data collection using in-depth interviews. The data were then analyzed using a qualitative descriptive analysis. The results of this study indicate that the forms of addiction in adolescents who play the game "Higgs Domino Island" are ambitions that are high enough to win big enough in the internet game Higgs Domino Island and the desire to earn money instantly through playing games. Then the intensity of addiction to playing games ranges from 1 to 3 hours a day. The source of addiction to the Higgs Domino Island game is lack of self-control from teenagers and also the environment or friends that influence today's youth to join in playing the Higgs Domino Island game. Suggestions for further research are that teenagers who play the game "Higgs Domino Island" should be given an intervention in order to reduce or stop the effects of addiction to playing games experienced by teenagers today.